Complex torcular dural arteriovenous fistula leading to cortical venous reflux-induced severe varix and subsequent bilateral cerebral hemispheric hemorrhage: a case report - Li, Ziqi; Hou, Pengwei; Chen, Qizuan; Mu, Shuwen; Li, Jun; Fang, Yi; Jiang, Wenting; Tian, Xinhua; Wang, Shousen (Frontiers in Neurology, 2023)
Background and importance Dural arteriovenous fistulas (dAVFs) with cortical venous reflux (CVR) are associated with a higher incidence of intracranial hemorrhage (ICH). We report a rare case of a complex torcular dAVF with severe cortical veins (CV) varix leading to extensive bilateral cerebral hemorrhages. This discovery suggests a potential new subtype of dAVF. The case underscores the necessity of a comprehensive understanding of hemodynamic changes in dAVFs and the importance of considering venous compensatory capacity in treatment. This case challenges existing classifications and treatment strategies for dAVFs, highlighting the need for further research and discussion within the neurosurgical community. Clinical presentation A 56-year-old male was admitted to the hospital presenting with dizziness, fatigue, and numbness. Brain CT scans revealed extensive bilateral cerebral hemorrhages. Digital subtraction angiography (DSA) identified a complex torcular dAVF. No cerebral sinus venous thrombosis was detected, but a venous variation in the left transverse sinus was observed. Preoperative DSA demonstrated the patient’s well-developed venous compensatory ability. Subsequently, the patient underwent transarterial embolization. The patient made a good recovery. Follow-up DSA and MR angiography at 3 months and 1 year post-treatment showed no recurrence. Conclusion DAVFs are rare lesions, prone to ICH, particularly when CVR is involved. We report a rare case of CVR with severe varix leading to hemorrhagic lesions in both cerebral hemispheres. Our aim is to alert neurosurgical colleagues worldwide to this potential new subtype and to evaluate treatment options, in order to assist those who may encounter such cases in the future.